Picture Coloring Play Therapy Affects Pre-School Children's Anxiety Levels During Hospitalization in St. Theresia Room Gunung Maria Tomohon Hospital - Patandung, Vina Putri; Langingi, Ake Royke Calvin; Rembet, Ignatia Yohana (PT FORMOSA CENDEKIA GLOBAL, 2024)
Hospitalization can be a distressing experience for children, leading to anxiety due to unfamiliar environments, treatments, and procedures. This study aimed to analyze the effect of coloring picture play therapy on anxiety levels in hospitalized preschool children at St. Theresia Room, Gunung Maria Tomohon Hospital. Using a pre-experimental pre-post test design, 15 preschool children were sampled through non-probability sampling. The Wilcoxon test and the Zung-Self Rating Anxiety Scale (ZSAS) were used for analysis. Results showed a significant effect of coloring picture play therapy on reducing anxiety, with a p-value of 0.001 < α = 0.05. The study concludes that coloring picture play therapy effectively reduces anxiety in hospitalized preschool children.